Higher Wheal Sizes of Dermatophagoides farinae Sensitization Exhibit Worse Nasal Symptoms in Allergic Rhinitis Patients - Nur Husna, Siti Muhamad; Md Shukri, Norasnieda; Tan, Hern-Tze Tina; Mohd Ashari, Noor Suryani; Wong, Kah Keng (Frontiers in Medicine, 2022)
Allergic rhinitis (AR) is a global health burden and it manifests in both nasal and non-nasal symptoms. Skin prick test (SPT) is a routine procedure to diagnose AR sensitized to common allergens including house dust mites (HDMs). The degree of sensitivity of a patient towards allergens is determined by the size of the wheal formed by SPT procedure. SPT wheal sizes are influenced by recent anti-histamine usage, however it remains unclear if SPT wheal sizes are also influenced by other factors. In this study, we set out to investigate the association between SPT wheal sizes with the demographical, clinical and environmental characteristics, as well as nasal and non-nasal symptoms severity scores, of AR patients (n=30) sensitized to common HDMs (i.e. Dermatophagoides pteronyssinus, Dermatophagoides farinae, and Blomia tropicalis). We showed that SPT wheal sizes of HDM allergens were not associated with clinical, demographical and environmental characteristics examined. Nonetheless, significant correlations were observed between SPT wheal sizes of D. farinae sensitization with worse severity scores of all five nasal symptoms examined (i.e. sneezing, runny nose, itchy nose, congestion and postnasal drip) and four of the six non-nasal symptoms examined (i.e. throat symptoms, ear symptoms, headache and mental function). Such relationships were not observed in SPT wheal sizes of D. pteronyssinus and B. tropicalis sensitization. We suggest that increased SPT wheal sizes for D. farinae sensitization may predict the likelihood of more severe nasal and, to a lesser extent, non-nasal manifestations in AR patients sensitized to HDMs.